Addition of Mesenchymal Stem Cells to Autologous Platelet-Enhanced Fibrin Scaffolds in Chondral Defects: Does It Enhance Repair?. (6th January 2016) - Goodrich, Laurie R.; Chen, Albert C.; Werpy, Natasha M.; Williams, Ashley A.; Kisiday, John D.; Su, Alvin W.; Cory, Esther; Morley, Paul S.; McIlwraith, C. Wayne; Sah, Robert L.; Chu, Constance R.
Abstract : Background: The chondrogenic potential of culture-expanded bone-marrow-derived mesenchymal stem cells (BMDMSCs) is well described. Numerous studies have also shown enhanced repair when BMDMSCs, scaffolds, and growth factors are placed into chondral defects. Platelets provide a rich milieu of growth factors and, along with fibrin, are readily available for clinical use. The objective of this study was to determine if the addition of BMDMSCs to an autologous platelet-enriched fibrin (APEF) scaffold enhances chondral repair compared with APEF alone. Methods: A 15-mm-diameter full-thickness chondral defect was created on the lateral trochlear ridge of both stifle joints of twelve adult horses. In each animal, one defect was randomly assigned to receive APEF+BMDMSCs and the contralateral defect received APEF alone. Repair tissues were evaluated one year later with arthroscopy, histological examination, magnetic resonance imaging (MRI), micro-computed tomography (micro-CT), and biomechanical testing. Results: The arthroscopic findings, MRI T2 map, histological scores, structural stiffness, and material stiffness were similar (p > 0.05) between the APEF and APEF+BMDMSC-treated repairs at one year. Ectopic bone was observed within the repair tissue in four of twelve APEF+BMDMSC-treated defects. Defects repaired with APEF alone had less trabecular bone edema (as seen on MRI) compared with defects repaired with APEF+BMDMSCs. Micro-CT analysis showed thinner repair tissue in defects repaired with APEF+BMDMSCs than in those treated with APEF alone (p < 0.05). Conclusions: APEF alone resulted in thicker repair tissue than was seen with APEF+BMDMSCs. The addition of BMDMSCs to APEF did not enhance cartilage repair and stimulated bone formation in some cartilage defects. Clinical Relevance: APEF supported repair of critical-size full-thickness chondral defects in horses, which was not improved by the addition of BMDMSCs. This work supports further investigation to determine whether APEF enhances cartilage repair in humans.